ASSOCIATION OF CLINICAL AND GENETIC FACTORS WITH LEFT VENTRICLE HYPERTROPHY IN ARTERIAL HYPERTENSION - T. Yu. Kuznetsova; D. V. Gavrilov; L. M. Samohodskaya; D. V. Rebrikov; S. A. Morozova; P. I. Makarevich; A. V. Kolotvin; A. B. Balatsky; A. Yu. Postnov; S. A. Boitsov (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate association of clinical and genetic factors with left ventricle hypertrophy (LVH) in patients with arterial hypertension (HT).Materials and methods. 672 patients with HT were involved, aged 50,6 y.o. in average, men 67%. Laboratory assays, ECG, echocardiography were performed. Control group included 184 healthy persons. Genotyping with single-nucleotide substitutions of the endothelial NO synthase (eNOS) Glu298Asp gene, the C242T of the NADPH oxidase p22phox subunit and the angiotensin 2 receptor type 1 А1166С gene was carried out using a polymerase chain reaction (PCR) with evaluating of restriction fragments length polymorphism, while with substitutions of the angiotensinogen М235Т, G(-6)A gene allele-specific PCR “in real time” was applied.Results. LVH was found in 39% of patients. It was more frequent in persons above 50 years old (OR 2,8, р<0,0001), in men (OR 1,43, p=0,035), in HT of degree 2-3 (OR 3,35, р<0,0001), HT duration more than 5 years (OR 2,52, р<0,05), in obesity (OR 1,57, р=0,005) or diabetes (OR 3,33, р<0,0001) presence. At genetic factors evaluation decrease of LVH risk was revealed in persons with the MM polymorphism of the angiotensinogen М235Т gene (OR 0,506, р=0,0187). Association of the MM genotype with LVH risk lowering was more obvious at the young age (OR 0,31, р=0,018). The A allele of the eNOS gene Glu298Asp polymorphism increased risk of LVH development when HT was diagnosed in the young age (OR 1,98, р=0,037) and in women up to 50 years old (OR 2,34, р=0,027). The T allele of the p22phox NADPH oxidase gene С242Т polymorphism correlated with LVH risk reduction in HT patients up to 50 years old (OR 0,6, p=0,01), the C allele – with increase of it (OR 1,66, р=0,01), this influence was more noticeable in women up to 50 years old (T allele – OR 0,21; C allele – OR 4,57, p=0,001).Conclusion. Hypertensive LVH correlates with age, male gender, HT degree and duration, obesity and diabetes mellitus. Genetic factors were less associated with LVH.